Analyzing the role of phytochemicals in targeting drug transporter protein ABCC6 using molecular docking and molecular dynamics simulations (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Triple negative breast cancer (TNBC) is an aggressive breast cancer subtype that lacks hormonal receptors. This reduces the therapeutic options for TNBC patients creating more focus on chemotherapy. Drug resistance has posed as a major hurdle in treating TNBC patients. Deregulation of drug transporter proteins is one of major factors that cause resistance to chemotherapeutic drugs. In this study, ABCC6 a drug transporter protein that is found dysregulated in several resistant cancer cells has been docked with natural compounds or phytochemicals with known anti-cancer activities. Subtrifloralactone G, a withanolide extracted from Deprea subtriflora is found to show highest binding energy with ABCC6 protein. Molecular dynamics simulations further prove the stability of the ABCC6 protein- Subtrifloralactone G ligand complex. ADMET analysis shows that phytochemical Subtrifloralactone G can be used as an anti-cancer therapeutic drug in treating resistant cancer cells. The study mainly focuses on the role of phytochemicals in treating resistant TNBC cells.